Effects of Toceranib Phosphate on Systolic Blood Pressure and Proteinuria in Dogs. (6th May 2016) - Tjostheim, S.S.; Stepien, R.L.; Markovic, L.E.; Stein, T.J.
Abstract : Background: Systemic hypertension and proteinuria are established adverse effects of tyrosine kinase inhibitor treatment in people. Objective: The objective of this study was to investigate changes in systolic blood pressure and the incidence of proteinuria secondary to treatment with toceranib phosphate in dogs with cancer. Animals: Twenty‐six control dogs and 30 dogs with cancer were evaluated for the first part of the study (baseline characteristics). For the second part (effect of toceranib phosphate treatment), 48 client‐owned dogs were evaluated, including 20 control dogs and 28 dogs with various types of neoplasia. Methods: Prospective cohort study. Client‐owned healthy control dogs and dogs with cancer were enrolled. Blood pressure and urine protein:creatinine ratios were measured before treatment and 2 weeks after initiation of toceranib phosphate treatment. Results: Systolic blood pressure was significantly ( P = 0.0013) higher in previously normotensive treatment dogs after initiation of treatment with toceranib phosphate (152 mmHg ± 19) compared to baseline (136 mmHg ± 14). 37% of treated dogs developed SBP ≥ 160 mmHg. The prevalence of systemic hypertension (37%) and proteinuria (21%) at baseline in treatment dogs did not differ from that of age‐matched healthy controls (15% [ P = 0.13] and 0% [ P = 0.069], respectively). Conclusions and Clinical Importance: Toceranib phosphate treatment might result in increased systolic blood pressures in dogs. Systemic hypertension should be considered a potential adverse effect of this drug in dogs. Systemic hypertension and proteinuria were detected at clinically relevant frequencies in the dogs with cancer before antineoplastic therapies suggesting that monitoring of these variables might be warranted in this population.